Income redistribution, consumer credit, and keeping up with the riches - Mathias Klein; Christopher Krause (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
In this study, we set up a DSGE model with upward looking consumption comparison and show that consumption externalities are an important driver of consumer credit dynamics. Our model economy is populated by two different household types. Investors, who hold the economy's capital stock, own the firms and supply credit, and workers, who supply labor and demand credit to finance consumption. Furthermore, workers condition their consumption choice on the investors' level of consumption. We estimate the model and find a significant keeping up-mechanism by matching business cycle statistics. In reproducing credit moments, our proposed model significantly outperforms a model version in which we abstract from consumption externalities.
Keywords: E21; E32; E44; 330; income redistribution; consumer credit; relative consumption motive; business cycles